Patient Characteristics and Survival Outcomes of Non-Metastatic, Non-Clear Cell Renal Cell Carcinoma - An, Josiah; Packiam, Vignesh T.; Chennamadhavuni, Adithya; Richards, Jordan; Jain, Jayanshu; Mott, Sarah L.; Garje, Rohan (Frontiers in Oncology, 2022)
Background Non-clear cell renal cell carcinoma (ccRCC) includes histologically and molecularly distinct subtypes such as papillary, chromophobe, collecting duct, and sarcomatoid RCC, with an incidence ranging from 20% to 25%. Oncologic outcomes and the role of adjuvant systemic therapy [vascular endothelial growth factor inhibitor (VEGFi) or immunotherapy] for non-ccRCC are not well-described. Objective To assess the incidence and survival outcomes of non-ccRCC subtypes in comparison to ccRCC. Methods The National Cancer Database was utilized to identify patients with non-metastatic RCC (T1–T4, N0–N1) between 2004 and 2015. The non-ccRCC cohort was further stratified by histologic subtype: papillary, chromophobe, sarcomatoid, and collecting duct RCC. Multivariable Cox regression models were used to compare overall survival (OS). Results The 5-year OS for chromophobe, papillary, clear cell, collecting duct, and sarcomatoid RCC was 91%, 82%, 81%, 44%, and 40%, respectively. After adjusting for clinicopathologic and treatment characteristics, there was no significant difference in OS between papillary RCC and ccRCC (p = 0.17). Patients with collecting duct and sarcomatoid subtypes were at over two times increased risk of death compared to patients with clear cell (p < 0.01 and p < 0.01, respectively). Conversely, patients with chromophobe RCC were at 36% decreased risk of death compared to ccRCC (p < 0.01). Conclusions This hospital-based analysis confirms that collecting duct and sarcomatoid histologic subtypes are uncommon and associated with poor survival after surgery when compared to the other RCC subtypes. Further studies are needed to evaluate the role of neoadjuvant and adjuvant systemic therapies in these subtypes to improve oncologic outcomes.